The economic marine tourism based on cleanliness health safety and environment (CHSE) protocol as covid-19 outbreak responses at Derawan Island, Indonesia. Issue 1 (January 2022) - Utami, P B; Parluhutan, D; Taryono, K; Auliansyah; Simarangkir, O R; Ricky; Nani
Abstract: Popular tourism activities at Derawan Island are snorkelling and diving. The Covid-19 outbreak led these activities down and reduced visitors and income for restaurant, lodging, and diving center business units. The Ministry of Tourism and Creative Economic of Indonesia (KEMENPAREKRAFT) issued a new regulation to suppress the pandemic's adverse impact specifically designed for New Normal Tourism with CHSE. They created new trouble in business units' cash flow. It requires financial incentives and stimuli for its stability. This study assessed the tourists' WTP, evaluation using the CVM, which covered the cash flow with three schemes. The value of the WTP substituted to financial analysis and looked at the number of BEP. WTP value for each person was US 2.97, or about US 190, 636.28 - 288, 677.80 in a year. If the cash flow did not reach the BEP, it would have proposed the financial stimuli to be submitted to related stakeholders. The restaurant was the most business unit that needed several financial incentives. Restaurants faced difficulties to reach BEP in three schemes, and they needed around US 170, 422.54 - 247, 323.94 in a year for over 20 restaurants.